2014
DOI: 10.1111/psyp.12236
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the initial light reflex during affective picture viewing

Abstract: An initial reflexive constriction of the pupil to stimulation – the light reflex – is primarily modulated by brightness, but is attenuated when participants are under threat of shock (e.g. "fear-inhibited light reflex").The present study assessed whether the light reflex is similarly attenuated when viewing emotional pictures. Participants viewed erotic, violent, and neutral scenes that were matched in brightness; as an additional control, scrambled versions identical in brightness were also presented. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
79
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 12 publications
12
79
1
Order By: Relevance
“…In recent studies, we found both attenuation of the initial light reflex and enhanced late pupil diameter when viewing highly arousing pleasant or unpleasant, compared to neutral, pictures during free viewing (Bradley et al, ; Henderson, Bradley, & Lang, ), and in the current study, we presented both emotionally arousing and neutral scenes. In their previous study assessing pupil diameter and emotional memory, Võ et al () reported that recognition of old words prompted larger pupil diameter than new words, regardless of whether words were emotional or neutral.…”
supporting
confidence: 60%
“…In recent studies, we found both attenuation of the initial light reflex and enhanced late pupil diameter when viewing highly arousing pleasant or unpleasant, compared to neutral, pictures during free viewing (Bradley et al, ; Henderson, Bradley, & Lang, ), and in the current study, we presented both emotionally arousing and neutral scenes. In their previous study assessing pupil diameter and emotional memory, Võ et al () reported that recognition of old words prompted larger pupil diameter than new words, regardless of whether words were emotional or neutral.…”
supporting
confidence: 60%
“…Pupil diameter is modulated by emotional arousal in a number of different contexts, including picture viewing, in which larger changes in pupil diameter are found when viewing highly arousing pleasant or unpleasant, compared to neutral, scenes (Bradley, Miccoli, Escrig, & Lang, 2008; Ferrari et al, 2015; Henderson, Bradley & Lang, 2014, Snowden et al, 2016). Pupil dilation has also been reported when participants listen to pleasant or unpleasant, compared to neutral, sounds (Partala & Surakka, 2003), and when participants anticipate the upcoming presentation of an aversive event.…”
mentioning
confidence: 99%
“…The content of the resulting images is no longer recognizable but colour and mean image luminance are retained (for similar approaches, see [1,17]).
Figure 1.Example stimuli of dressed, blurred and naked women and men, and the corresponding control images.
…”
Section: Methodsmentioning
confidence: 99%